2016
DOI: 10.1038/cdd.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 and HDAC2 in mouse oocytes and preimplantation embryos: Specificity versus compensation

Abstract: Oocyte and preimplantation embryo development entail dynamic changes in chromatin structure and gene expression, which are regulated by a number of maternal and zygotic epigenetic factors. Histone deacetylases (HDACs), which tighten chromatin structure, repress transcription and gene expression by removing acetyl groups from histone or non-histone proteins. HDAC1 and HDAC2 are two highly homologous Class I HDACs and display compensatory or specific roles in different cell types or in response to different stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 90 publications
(149 reference statements)
5
54
0
Order By: Relevance
“…In summary, GO term analysis offered no striking outliers in functional categories within our screen results and suggests that preimplantation development equally requires all aspects of cellular and molecular function for success. Supporting this notion, previous studies have found essential roles during preimplantation for genes within each of these functional categories (including DNA/RNA/protein binding4546, catalytic activity4748, various transporter activity495051). …”
Section: Resultsmentioning
confidence: 70%
“…In summary, GO term analysis offered no striking outliers in functional categories within our screen results and suggests that preimplantation development equally requires all aspects of cellular and molecular function for success. Supporting this notion, previous studies have found essential roles during preimplantation for genes within each of these functional categories (including DNA/RNA/protein binding4546, catalytic activity4748, various transporter activity495051). …”
Section: Resultsmentioning
confidence: 70%
“…The biological activities of HDAC1 in embryogenesis appear to be distinct among HDAC isoforms and may differ from the HDAC1 functions in somatic cells of various differentiation lineages (45). Future studies are warranted to address whether the lack of maspin-mediated control of HDAC1 activity underlies the embryonic lethality of Maspin KO mice, and whether the cell type-specific expression of maspin and its inhibitory interaction with HDAC1 in embryogenesis are distinct from those in somatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…H3K9ac and H3K14ac exist in these active transcription regions to create a microenvironment for recruiting transcriptional factors and RNA polymerase II at the GV stage in oocytes (Kim et al 2003, De La Fuente et al 2004, Gu et al 2010, Ding et al 2012. After meiosis resumes at the GVBD stage, these acetylations are removed by histone deacetylases (HDACs) to further condense the chromatin for meiotic division (Akiyama et al 2004, Ma & Schultz 2016.…”
Section: Histone H3 Acetylation In Meiosismentioning
confidence: 99%